The potential protective effects of curcumin against diet-induced neonatal programming of metabolic dysfunction in growing rats - Ibrahim, Kasimu Ghandi (My University, 2019)
The current global epidemic of metabolic syndrome in children and adolescents, though driven in part by increased consumption of fructose-rich diets, has been linked to nutritional perturbations in critical developmental periods. Plant-derived polyphenols when administered during the suckling period have been shown to program for protection against diet-induced metabolic dysfunction in childhood or adolescence. Curcumin, a hydrophobic polyphenol extracted from turmeric, has antioxidant, anti-diabetic and anti-obesity properties. It was hypothesised that the oral administration of curcumin during the suckling period would protect against the development of high fructose-induced metabolic dysfunction in adolescence. One hundred and twenty-eight 6-day old suckling Sprague-Dawley pups (65 males; 63 females) were initially randomly allocated to four treatment groups and administered with either a 0.5% dimethyl sulfoxide (vehicle control), 500mg.kg-1 body mass of curcumin, fructose (20%, w/v) or a combination of curcumin and fructose. The treatments were administered once daily via oral gavage at 10ml.kg-1 body mass from postnatal day 6 to 21 in order to induce programming. At postnatal day 21, the rats were weaned onto normal rat chow. Each of the initial groups was subdivided into two subgroups: one had only plain tap water while the other had fructose (20%, w/v) as their drinking solution from postnatal day 21 to 63 when the rats were euthanised and tissues collected for analyses. In both sexes the metabolic responses of the rats (fasting plasma glucose, triglycerides, total cholesterol, insulin and adiponectin concentration) were similar (p>0.05, ANOVA) across the treatment groups. Feeding with fructose only in the postweaning period induced mesangial proliferation and mild tubular secretions in the male rats; and moderate glomerular atrophy, increased Bowman capsular space and increased tubular secretions in the female rats. In both sexes, neonatal administration of curcumin prevented the postweaning fructose only-induced changes in kidney tissues. Administration of curcumin during the suckling period with no fructose at all caused glomerular atrophy, increased Bowman capsular space and mild to moderate tubular secretions in both male and female rats. In both sexes, fructose administration induced marked hepatic inflammation (p= 0.0015 males, p= 0.0112 females, Kruskal Wallis) and hepatic fibrosis (p<0.0001, ANOVA), the hallmarks of non-alcoholic steatohepatitis, which were prevented by the neonatal oral administration of curcumin. The hepatic gene expression ratios for 5’ Adenosine-monophosphate activated protein kinase alpha (AMPKα) in both sexes were significantly downregulated (p<0.0001, ANOVA). The vii expression ratios of tumour necrosis factor alpha (TNFα) were significantly upregulated (p<0.0001) in rats fed a high fructose diet pre and/or postweaning compared to the other groups. Male rats administered with curcumin and fructose pre-weaning and fed a high fructose diet post weaning had significantly shorter femora (p= 0.0038, ANOVA) compared to their counterparts administered a similar treatment pre-weaning and plain tap water postweaning. Male rats that received curcumin alone or curcumin and fructose during the suckling period and subsequently fed a high fructose diet had significantly lower (p≤0.05, ANOVA) plasma total osteocalcin concentration compared with that from rats in other treatment groups. In female rats, administration of curcumin alone or curcumin and fructose during the suckling period and subsequent feeding with high fructose resulted in significantly lower (p≤0.05, ANOVA) osteocalcin concentration compared to administration of DMSO during suckling and then feeding with a high fructose diet post weaning. Both male and female rats had similar (p>0.05, ANOVA) leucocyte telomere lengths across the treatment groups. Neonatal oral administration of curcumin programmed for protection against non-alcoholic steatohepatitis, kidney injury and increased bone turnover induced by a postweaning high fructose diet. Therefore, the administration of oral curcumin during the suckling period could potentially protect against the high fructose diet-induced liver, kidney and bone diseases in adolescence and can be useful in mitigating the current epidemic.
A thesis submitted to the Faculty of Health Sciences, School of Physiology, University of the Witwatersrand, in fulfilment of the requirements for the degree of Doctor of Philosophy